Tell this to the universe - Prince, Katie (Poet) (YesYes Books, 2024)
"There is an absence at the heart of Katie Prince's debut collection, Tell This to the Universe, and an obsessive search to find what's missing. Like moons around faraway planets, the poems orbit the strange and brutal landscapes of longing, alienation, and grief as they move through physics to philosophy, linguistics to mathematics, fairy tales to science fiction. It could be said that this book is trying to find god-to name it, to hurt it or hold it, to make desperate demands of it-but it's just as true to say it's looking for a home, a family, an answer to a question it still doesn't know how to ask."